Plasmacytoid dendritic cells during infancy are inversely associated with childhood respiratory tract infections and wheezing - Upham, J.; Zhang, Guicheng; Rate, A.; Yerkovich, S.; Kusel, M.; Sly, P.; Holt, P. (Mosby, Inc., 2009)
Background: It has been proposed that immune dysfunction during early childhood plays an important role in asthma pathogenesis. However, it is not known specifically whether changes in dendritic cells (DCs) during infancy antedate the development of respiratory tract infections, asthma, and related clinical phenotypes. Objectives: We sought to assess the association between the level of blood DCs during the first year and the subsequent development of respiratory tract infections, wheezing, and allergic sensitization. Methods: A community-based cohort of children with a family history of atopy was followed to age 5 years. Children were monitored intensively for respiratory tract infections. History of wheeze and asthma was collected annually, atopy was documented at 5 years, and flow cytometry was used to identify DC subsets in blood samples collected when children were well. Results: Levels of plasmacytoid DCs (pDCs) during infancy were inversely correlated with symptoms of lower respiratory tract infections, parent-reported wheezing, and the cumulative rate of physician-diagnosed asthma up to age 5 years. These relationships were independent of atopy, as determined by allergy skin test results and total and specific IgE levels. In contrast, levels of myeloid DCs were not associated with respiratory tract infections, asthma, or wheezing but were associated with total IgE levels at age 5 years. Conclusion: In children with a family history of atopy, relative deficiency of circulating pDCs during infancy appears to be a risk factor for more frequent and more severe respiratory tract infections, wheezing, and a diagnosis of asthma. Infants with higher numbers of pDCs are protected against these outcomes. © 2009 American Academy of Allergy, Asthma & Immunology.